Viral etiology of acute respiratory infections in children in Southern Iran - Mehrdad Halaji; Tayebeh Hashempour; Javad Moayedi; Gholam Reza Pouladfar; Behzad Khansarinejad; Reza Khashei; Afagh Moattari; Zahra Musavi; Farzaneh Ghassabi; Neda Pirbonyeh (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: Prevalence of influenza A virus (Flu-A), respiratory syncytial virus (RSV), and human metapneumovirus (hMPV) was assessed in children with acute respiratory infections (ARIs). METHODS: Nasopharyngeal aspirates and throat swabs were subjected to real-time polymerase chain reaction (PCR) to detect RSV and Flu-A and to conventional PCR to detect hMPV. RESULTS: Of the 156 children assessed, 93 (59.6%) carried at least one virus, with 35.9% positive for RSV, 14.1% for hMPV, and 9.6% for Flu-A. The prevalence of co-infections was 2.6%. CONCLUSIONS: The high detection rate may reflect increased sensitivity of real-time PCR compared to traditional PCR and viral culture.